Online Learning During the Covid-19 Pandemic: How has this New Situation Affected Students' Oral Communication Skills? - Jesús García Laborda (National Research University Higher School of Economics, 2021)
Employing technology has become imperative to accelerate learning efforts and offer methods to enhance interactions between learners, and among learners and tutors. In this paper, we investigate the difficulties faced by learners in learning virtually and, specifically, in English language learning, with a focus on oral communication skills. Research questions of this study are related to the main difficulties that students face to enhance their English oral communication skills. The tools and methodologies that worked best for them for this purpose are also in focus. In the literature we present a review of pertinent studies connected with learning responses in the COVID-19 period and those specifically related to the topic of our study. The methodology used for the study was an exploratory survey research design using a questionnaire to collect the necessary data for our research. Results showed that students highlighted technical problems as some of the main challenges, as well as not feeling completely comfortable in the online learning environment due to the lack of real communication, which also had an impact in the perception of their progress. They also found group video or audio calls to be the most useful tool for communication purposes. The results of this preliminary study are relevant to educational developers and policymakers. They give an understanding of aspects to be considered to improve the efficacy of learners' when it comes to enhancing their English communication skills, such as difficulties regarding interaction or level of satisfaction in an online learning environment.